Allometric model for quantification of sorghum canopy formation - Narayanan, Sruthi; Aiken, Robert M.; Paul, George (My University, 2011)
Canopy architecture has a prominent role in fundamental processes of crop growth including light transmission and interception, evapotranspiration and photosynthesis. Leaf Area Index (LAI)is a commonly used parameter for analyzing vegetative canopy structure and it can directly quantify canopy architecture (Welles and Norman, 1991). Tewolde et al. (2005) identified LAI as the key parameter in the analysis of crop growth and productivity. Leaf area index and total dry matter increment determine the transpiration efficiency and water use efficiency in a sparse crop (Kato et al., 2004). Quantification of LAI has potential in understanding resource use efficiency and productivity of a crop. Several complex models have been proposed to simulate leaf area index (LAI) in sorghum (Sorghum bicolor (L.) Moench) (Hammer et al., 1993), but a thorough inclusion of total mature and immature leaf area is lacking in these models. Objective: Develop a simple quantitative model to predict LAI for sorghum from emergence to flag leaf stage.
Keywords: Leaf area; Leaf Area Index (LAI); Phyllochron; Leaves; Sorghum; Canopy formation